Clustering of Entrepreneurial Profiles of University Students at UNALM: An Analysis with K-Means - Antonio Vargas, Javier Rubén (2025)
This study classifies the entrepreneurial profiles of students enrolled in the Business Development course at the National Agrarian University La Molina (UNALM), analyzing the variables of gender, age, and field of study. A non-experimental quantitative methodology was employed, using a survey validated by the Wadhwani Foundation, followed by a cluster analysis with the K-Means algorithm. The results identified two clusters of students with entrepreneurial tendencies and revealed a significant relationship between gender, age, and field of study with entrepreneurial profiles. Findings indicate that each student exhibits at least one type of entrepreneurial style, with certain profiles being more prevalent depending on gender and field of study. This study provides valuable insights for designing educational programs that foster entrepreneurship among diverse student groups.